2015
DOI: 10.1016/j.pocean.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

On the surprising lack of differences between two congeneric calanoid copepod species, Calanus finmarchicus and C. helgolandicus

Abstract: The important calanoid copepod species Calanus finmarchicus and C. helgolandicus have distinct geographic ranges which are changing under the influence of climate change. Understanding the mechanisms underlying their distributions is becoming increasingly important as a result of the possible ecological impacts of these range shifts. Here we review inter-species differences in key life cycle traits that influence each species’ geographic distribution, in particular development and growth, fecundity, feeding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 159 publications
(337 reference statements)
1
36
0
Order By: Relevance
“…Field observations of size in relation to temperature in C. finmarchicus and C. helgolandicus across the North Atlantic show a similar relationship (Q 10 = 1.65, Wilson et al, 2015, with prosome length converted to carbon weight based on Runge et al, 2006). Somewhat surprisingly, even wide variation in prey conditions (clusters of gray dots, Figure 4) has only minor effects on this slope.…”
Section: Global Behaviormentioning
confidence: 72%
See 1 more Smart Citation
“…Field observations of size in relation to temperature in C. finmarchicus and C. helgolandicus across the North Atlantic show a similar relationship (Q 10 = 1.65, Wilson et al, 2015, with prosome length converted to carbon weight based on Runge et al, 2006). Somewhat surprisingly, even wide variation in prey conditions (clusters of gray dots, Figure 4) has only minor effects on this slope.…”
Section: Global Behaviormentioning
confidence: 72%
“…C. finmarchicus, for example, is fit well by u 0 = 0.007 d −1 at higher temperatures (4-12 • C), whereas near 0 • C in Disko Bay, it has been observed to be considerably smaller than extrapolation along the u 0 = 0.007 d −1 power law would predict. Past studies have also found C. finmarchicus growth and ingestion FIGURE 4 | Relationship between adult size W a and mean surface temperature T 0 in the "global" model experiment, for three values of relative development rate u 0 , in comparison with observations (Peterson, 1986;Swalethorp et al, 2011;Wilson et al, 2015;Campbell et al, in press) and laboratory results (Campbell et al, 2001;Rey-Rassat et al, 2002). Model results (gray dots) represent structural biomass S, as do observations marked with a ⋆; observations marked with a • represent total biomass R + S. Clusters of gray dots indicate families of model cases varying productive season length (horizontal axis in Figure 5).…”
Section: Global Behaviormentioning
confidence: 86%
“…However, while there is a comprehensive amount of literature on the lipid deposition and overwintering dynamics of the arcto-boreal C. finmarchicus, the spares literature on the similar issues for the temperate C. helgolandicus indicates that lipid deposition is much less (Rey-Rassat et al, 2002) and too low for bringing the latest copepodite stages through the winter dark with a positive energy balance. Moreover, Wilson et al (2015) found "no direct evidence that C. helgolandicus undergoes a period of diapause." We do not know whether future life cycle adaptation (i.e., large lipid deposition and overwintering) would be possible for temperate species like C. helgolandicus.…”
Section: Zooplankton Distributionmentioning
confidence: 97%
“…We hypothesize that the latitudinal change in bloom dynamics determined by the destined and stable latitudinal-dependent seasonal light cycle represents a fundamental barrier at high latitudes to the onward climate change-induced migration of temperate-adapted planktivorous from lower latitudes, unless they are able to adapt by depositing lipids and undertake overwintering. C. helgolandicus with its core production area to the south of the North Atlantic Current is a copepod species that is known to deposit only limited amounts of lipids and with no clear evidence of overwintering response (Wilson et al, 2015). There is no need since this temperate species can feed during winter, although less so than during spring/summer/autumn.…”
Section: Zooplankton Distributionmentioning
confidence: 99%
See 1 more Smart Citation